Adolescent Smoking Behavior In Indonesia; A Longitudinal Study - Radian Ilmaskal; Linda Wati; Rischa Hamdanesti; Alkafi Alkafi; Helmanis Suci (Eduvest - Journal of Universal Studies, 2022)
Adolescent smoking behavior in Indonesia is increasing every year. This condition is dangerous threat to the sustainability of a country. This study was aimed to analyze determinant factors related to adolescent smoking in Indonesia. The study is quantitative research with cross sectional design. This study utilized IFLS 5 data. Sample was unmarried adolescent aged 15-24 years with a total of 4,959 adolescents. Association between adolescent smoking behavior status with parental smoking habits, gender, age and residence were determined by using chi-square test. We found that the majority (93%) of adolescents were smokers who smoke a maximum of 10 cigarettes per day and most of them started smoking regularly at the age of 12 to 17 years (66%). Parental smoking habits significantly influenced adolescent smoking behavior (p=0.000; OR=1.397; 95% CI=1.173<OR<1.663). Gender and age group also affected smoking behavior in adolescents. Meanwhile, the classification of residence has no significant effect on adolescent smoking behavior (p=0.337; OR=0.920; 95% CI=0.777<OR<1.090). These findings suggested that efforts to prevent adolescent smoking behavior should be more focused on children who live with smoking parents.